Similar Midterm Outcomes of Total Knee Arthroplasties with Anterior and Posterior Tibial Slopes Performed on Paired Knees at a Minimum Follow-up of 5 Years - Song, Sang Jun; Bae, Dae Kyung; Hwang, Sung Hyun; Park, Hong Sik; Park, Cheol Hee (The Journal of Knee Surgery, 2023)
A small posterior tibial slope (PTS) is generally recommended in posterior stabilized (PS) total knee arthroplasty (TKA). An unwanted anterior tibial slope (ATS), which can affect postoperative results, may be created in PS TKA because of the inaccuracy of surgical instruments and techniques, as well as high interpatient variability. We compared midterm clinical and radiographic results of PS TKAs with ATS and PTS performed on paired knees using the same prosthesis. One-hundred-twenty-four patients who underwent TKAs with ATS and PTS on paired knees using ATTUNE posterior-stabilized prostheses were retrospectively reviewed after a minimum follow-up period of 5 years. The mean follow-up period was 5.4 years. The Knee Society Knee and Function scores, Western Ontario and McMaster Universities Osteoarthritis Index, Feller and Kujalar scores, and range of motion (ROM) were evaluated. The preferred TKA out of ATS and PTS was also investigated. The hip-knee-ankle angle, component positions, tibial slope, posterior femoral offset, Insall–Salvati ratio, and knee sagittal angle were measured by radiography. There were no significant differences in the clinical results, including ROM, between TKAs with ATS and PTS preoperatively and at the last follow-up. Regarding patient preference, 58 patients (46.8%) were satisfied with bilateral knees, 30 (24.2%) preferred knees with ATS, and 36 (29%) preferred knees with PTS. There was no significant difference in the rate of preference between TKAs with ATS and PTS (p = 0.539). Except for the postoperative tibial slope (−1.8 vs. 2.5 degrees, p < 0.001), there were also no significant differences in the radiographic results, including the knee sagittal angle, preoperatively and at the last follow-up. The midterm outcomes were similar between PS TKAs with ATS and PTS performed on paired knees at a minimum of 5 years of follow-up. Nonsevere ATS did not affect midterm outcomes in PS TKA with proper soft tissue balancing and the current prosthesis of improved design. However, a long-term follow-up study is required to confirm the safety of nonsevere ATS in PS TKA.Level of Evidence: III
Keywords: knee; arthroplasty; tibial slope; range of motion; knee sagittal angle